Comparison of supine and prone oriewntation in swimming - Pease, D. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to identify the differences in drag characteristics exhibited by a human form towed in a prone and a supine position below the water surface. Drag curves were established for both orientations over 13 velocities and 7 depths. From the results of a two way repeated measures ANOVA it was evident that while there is no practical difference between the two orientations at the greater depths, as depth decreases there is greater increase in drag force exhibited in the supine condition. There was a significantly greater drag force across all velocities (especially at those greater than 1.2ms-1) for the supine condition. These differences were up to 20N or approximately 40%. From these results it is recommended that athletes utilise a greater depth when kicking in a supine orientation in order to limit the influence of greater surface interactions and the associated increase in drag force.